An alternative approach to identify key industries: issues to selection criteria - Al-Amin, Abul Quasem; Jaafar, Abdul Hamid (Journal of Business Economics and Management, 2014)
Within a process of modeling exercise, this study aimed to understand appropriate selection criteria to identify key industries. There are many key sector identification linkage measures in the subject matter and sensitivity issue among them can be tricky because many of these measures differ only slightly but can result in outcomes that are quite dissimilar. With this background, we proposed an alternate approach that helps to resolve this issue. The proposed approach utilizes in this study by five sub-methods and high degree of the frequency of their occurrences in sub-methods to determine the key sectors. The study approach is applied to Malaysia as the public sector investment remains a large share in the national economy, like other developing countries, and the correct identification is still a challenge for sectoral planning. The experiences from this study can be used to guide appropriate public investment in Malaysia and elsewhere with similar economic forms.